2005
DOI: 10.1038/sj.bjc.6602642
|View full text |Cite
|
Sign up to set email alerts
|

mRNA quantification and clinical evaluation of telomerase reverse transcriptase subunit (hTERT) in intracranial tumours of patients in the island of Crete

Abstract: Telomerase is a reverse transcriptase that maintains telomeres by adding telomeric TTAGGG repeats to the ends of human chromosomes. The aim of this study was to evaluate quantitatively the mRNA expression of telomerase catalytic subunit (hTERT) in different types of intracranial tumours in relation to their histologic pattern and grade and correlate it with progression-free (PFS) and overall survival (OS) of patients. Human telomerase reverse transcriptase mRNA levels were estimated by the use of real time RT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Recent evidence showed that telomerase activity and hTERT were considerably higher in the tissues of many different cancers than in normal tissues, and that hTERT mRNA was detectable in all tumor cells possessing telomerase activity [6][7][8][9]. Higher telomerase activity and higher levels of hTERT mRNA expression correlated significantly with poor prognosis [10,11]. The most recent and significant advances in this area demonstrated that the inhibition or down-regulation of hTERT expression could inhibit telomerase activity and prevent the malignant proliferation of tumor cells [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence showed that telomerase activity and hTERT were considerably higher in the tissues of many different cancers than in normal tissues, and that hTERT mRNA was detectable in all tumor cells possessing telomerase activity [6][7][8][9]. Higher telomerase activity and higher levels of hTERT mRNA expression correlated significantly with poor prognosis [10,11]. The most recent and significant advances in this area demonstrated that the inhibition or down-regulation of hTERT expression could inhibit telomerase activity and prevent the malignant proliferation of tumor cells [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%